Intraoperative neuromonitoring in traditional and miniinvasive thyroidectomy. A single center experience in 1652 nerve at risk. - Nisi, Piercosimo; Piva, Giovanna; Cozzani, Federico; Rossini, Matteo; Bonati, Elena; Madoni, Cristiana; Bignami, Elena Giovanna; Del Rio, Paolo (Acta Biomedica Atenei Parmensis, 2020)
Background: The injury of laryngeal recurrent nerve (RLN) is one of the most severe adverse event in thyroid surgery. The rate in literature is reported as 2-11% for transient palsy and 0,6-1,6% for permanent palsy (after 6 months from surgical procedure). Aim of the Study: The aim of this study was to describe the frequency of the injury of RLN in our hospital during thyroid surgery, in which the IONM was applied. Materials and Methods: The patients undergoing thyroid surgery associated to Intraoperative Neuromonitoring (IONM were enrolled consecutively from 21/08/2014 to 30/08/2018. We collected data from I-IONM and not by Continuos IONM (C-IONM) because we have interrupted C-IONM after a case of cardiac arrest (15TH patient) during the APS placement. Results: The utility of the intraoperative neuro-monitoring system was evaluated with the following statistical methods: Mann Withney U-test with independent samples, T-samples with coupled samples, Wilcoxon signed sign test, Chi square test., Positive predictive value (PPV), Negative predictive value (NPV),we considered the values for p <0.05 statistically positive. Discussion: In high-volume centers the rate of transitory / permanent vocal cord palsy is low but also in these Units the need of feel safety is related to IONM. The use of the IONM is an helpful tool for dissection and anatomical identification of the nerves. IONM has a high specificity and sensitivity and a high negative predictive value. PPV as 52% definable low, may be related to the transient stupor of nerve function.